HUBUNGAN BERAT BADAN BAYI DENGAN ROBEKAN PERINIUM PADA PERSALINAN FISIOLOGIS DI PMB ANA SAWARAN LOR - siti zaenab; Tutik Ekasari; Homsiatur Rohmatin (NHM PRESS, 2023)
Perineal tears in normal delivery can be experienced by mothers who give birth to large fetal weight. So that pregnant women need to routinely monitor fetal weight during pregnancy to know the estimated fetal weight, and control a balanced and healthy diet. The purpose of this study is to analyze the correlation between infant weight and perineal tears in physiological labor at PMB Ana Sawaran Lor. Research design with cross-sectional. The sampling technique used a total sampling of 32 mothers giving birth. Respondent characteristic questionnaire and observation sheet of baby's weight and the incidence of perineal tears. While the test used the chi-square test. The results showed that the majority of mothers who gave birth experienced perineal tears as many as 18 respondents (56.2%). The majority of mothers giving birth have a normal newborn weight of 2500-3500 grams (53.1%). There is a significant correlation between a baby's weight and perineal tears in physiological delivery, namely p-value 0.000. Mothers giving birth with large baby weights are very at risk of experiencing perineal tears. .